(3ajV GdMb GdhOhO HHjGf YbGFO GdNdb aj hMOI GdhLhOs - (3fTGg eMeO jhSa Hf TGg eMeO YHO Gddg GdbGOQj GdJbTHfOj GdfjdhQjs ((3MjOQ CHGO s)
(3ChdgG (B:s
(3GdMeO ddg ehLO GdCTjGA Yf hLhOg HEYJHGQ GdaQOjI , GdeJfYe HhLhOGJg HMVQI GdGdhgjI CeG HYO gPg QSGdI eNJUQI LGeYI dCUhd eSGFd GdUhajI HWQjb Nai , haGQbI Hjf ePgH GdedMOjf hGdeMbbjf s
(3BNQgG (B:s
(3hGdOdjd Ydi efY EJHGY GdfaS bhdg Ld hYdG(B: (3Ef GdfaS dCeGdQi HGdShA JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B50s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs